Survival probabilities of stomach and colon cancer patients in Bangladesh - Ahammed, Tanvir; Akter, Mst Farzana; Suchana, Afroza Jannat; Chowdhury, Anisa Ahmed; Shah, Md Rafil Tazir; Rahman, Md Siddkur; Akter, Ayesha; Ullah, Mohammad Ohid (Asian Journal of Medical and Biological Research, 2020)
Cancer is predicted to be a progressively vital reason behind morbidity and mortality in the next few decades, in all regions of the world. In Bangladesh, about 150781 new cancer cases occur in 2018 and caused about 108137 deaths. Stomach and colon cancer have 6.3% and 2% of the total cancer deaths in Bangladesh. However, to the best of knowledge, no study has been conducted in Bangladesh on the survival probabilities of stomach and colon cancer patients. Therefore, we aimed to conduct a study on the survival probabilities of stomach and colon cancer patients with respect to sex, age, and body mass index. Only sixty-five patients with stomach or colon cancer from the eight divisional cities in Bangladesh were observed. A non-parametric, Kaplan-Meier product limit estimate for survival probabilities was utilized in this study. Less median survival time for female patients (22 months) than for males (31 months) was found. Almost similar patterns were observed for patients older than 45 years compared to younger patients and overweight patients. Taken together, this study suggests that male, younger and healthy weight patients’ survival probabilities are higher than female, older and overweight patients respectively. To avoid these kinds of diseases and increase survival probabilities, we should always take a balanced diet and doing exercise regularly to keep a healthy weight. Government and non-government organizations need to take proper steps to create awareness levels among the people as well. Asian J. Med. Biol. Res. March 2020, 6(1): 123-129